Website-Based TIQ Application for Mangrove Tourism Entrance Tickets for Pari City Village - Isnar Sumartono; Ahmad Akbar; Tway Wandiky Lumban Gaol (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This research aims to develop an entrance ticket application based on QR Code "TIQ" that can be used in Mangrove Tourism in Kota Pari Village. Kota Pari Village Mangrove Tourism is one of the popular tourist destinations that offers natural exploration and environmental education experiences. However, the admission system currently in use still uses manual methods that are prone to fraud and are time-consuming. Therefore, this research aims to introduce an efficient and safe QR Code-based admission ticket application. This research uses a software development method with the stages of needs analysis, system design, implementation, and testing. In the needs analysis stage, we conducted a survey of tourism visitors and management of Mangrove tourism in Pari City Village to understand the needs and obstacles that exist in the current entrance ticket system. Visitors can scan their QR Code when they arrive at the entrance, and the admission ticket information will be validated instantly by the system. The recorded entry ticket data will be stored in the database for monitoring and analysis purposes. The test results show that this QR Code-based admission ticket application can improve the efficiency and safety of the entrance ticket process at the Kota Pari Village Mangrove Tourism. Visitors can easily obtain their admission tickets and avoid long queues at the entrance. In addition, this system also reduces the potential for admission ticket fraud because each ticket has a unique code that is difficult to forge. This research contributes to the development of a technology-based admission ticket system in the tourism sector. This QR Code-based admission ticket application can be adopted by other tours to improve efficiency and visitor experience. In the end, it is hoped that this research can help improve the management and services in the Kota Pari Village Mangrove Tourism and provide better benefits for visitors and the local community.